2007
DOI: 10.1111/j.1365-2672.2007.03532.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Shiga toxin-producing Escherichia coli O26 in various manure-amended soil types

Abstract: This study provides useful information regarding the ecology of STEC O26 in manure-amended soils and may have implications for land and waste management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 42 publications
2
23
1
3
Order By: Relevance
“…Four strains of serotype 026:F111 were inoculated in manure-emended loam and clay loam soils at a level of approximately 6 log CFU/g. At 20°C, survival of the 026:H11 strains in emended soil ranged from 196 to >365 days, and at 4°C, the survival was 288 to >365 days (20). demonstrated that non-0157 STEC had prolonged survival in cattle waste such as manure or slurry and that non-0157 STEC survived for long periods in soil containing cow manure.…”
Section: Survival Of Stec In Cattle Manure and Soilmentioning
confidence: 95%
See 1 more Smart Citation
“…Four strains of serotype 026:F111 were inoculated in manure-emended loam and clay loam soils at a level of approximately 6 log CFU/g. At 20°C, survival of the 026:H11 strains in emended soil ranged from 196 to >365 days, and at 4°C, the survival was 288 to >365 days (20). demonstrated that non-0157 STEC had prolonged survival in cattle waste such as manure or slurry and that non-0157 STEC survived for long periods in soil containing cow manure.…”
Section: Survival Of Stec In Cattle Manure and Soilmentioning
confidence: 95%
“…STEC serotype 026:H11 survived for long periods in soils emended with cow manure (20). Four strains of serotype 026:F111 were inoculated in manure-emended loam and clay loam soils at a level of approximately 6 log CFU/g.…”
Section: Survival Of Stec In Cattle Manure and Soilmentioning
confidence: 99%
“…Although there are leafy green vegetable associated outbreaks caused by Salmonella and Cyclospora , a majority of them have been due to food contamination with Escherichia coli O157:H7 (Sivapalasingam et al, 2004). The most likely mechanisms of E. coli O157: H7 contaminations include contamination from soil amendments (i.e., manure, compost and compost teas), water (irrigation or flooding/runoff from adjacent land), wildlife, and airborne deposition from off-farm activities such as cattle/dairy and manure/composting operations (Franz et al, 2008, 2011; Fremaux et al, 2008; van Elsas et al, 2011). One of the worst incidents to date was a multistate Escherichia coli O157:H7 outbreak in August and September 2006, which was associated with consumption of fresh, bagged spinach that was traced to a field in California (California Food Emergency Response Team, 2007a,b; Cooley et al, 2007; Jay et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to temperature, the indigenous microflora (93), scarcity of nutrients (96), and protozoan predations also influence survival. Recent passage of VTEC through the bovine gastrointestinal tract may enhance survival of O157 in water (97).…”
Section: Vtec In Watermentioning
confidence: 99%
“…However, it should be noted that not all strains belonging to these serogroups will cause severe illness and that other non-O157 VTEC serogroups also cause illness. Pathogenic VTEC strains are categorized as enterohemorrhagic E. coli, and usually in these strains, a large outer membrane protein (94)(95)(96)(97) called intimin mediates the intimate contact between the bacterium and the enterocyte cytoplasmic membrane (attachment) and the destruction of the enterocyte microvilli (effacement). The genetic determinants for this (eae, tir, esc, and sep genes) are grouped together on the chromosome, forming a pathogenicity island called LEE, for locus of enterocyte effacement (7).…”
Section: Human Pathogenic Vtecmentioning
confidence: 99%